Validation of the SMOS Mission for Space Weather Operations: The Potential of Near Real‐Time Solar Observation at 1.4 GHz - M. Flores‐Soriano; C. Cid; R. Crapolicchio (Space Weather)
Abstract Soil Moisture and Ocean Salinity (SMOS) is an ESA mission observing Earth at 1.4 GHz with full polarimetry. SMOS images are affected by a noise of solar origin produced by the Sun appearing in the antenna's field of view. In this paper, we study whether this solar signal is of any use for scientific and space weather observations. We analyze the response of the SMOS Sun brightness temperature (BT) to thermal and nonthermal solar emissions, and compare them with observations from ground radio telescopes, GOES X‐ray flares, and CMEs from SOHO/LASCO. We find that the SMOS Sun BT can detect weak variations in the solar emission such as the progress of the 11‐year activity cycle, the solar rotation, and the thermal emission from flares. Solar radio bursts detected by the SMOS Sun BT are generally observed during flares from the visible hemisphere of the Sun that are associated with a CME. We also find a correlation between the amount of solar flux released at 1.4 GHz and the speed, angular width, and kinetic energy of the CMEs. We conclude that the unique capability of the SMOS mission to perform 24 h near real‐time observation of the Sun with full polarimetry makes it a promising instrument for monitoring solar interferences affecting GNSS, radar, and L‐band wireless communications, as well as for early assessment of flares geoeffectiveness. Nevertheless, the current limitations of the solar data as byproduct of the SMOS data reduction pipeline make it necessary to create a dedicated product for solar observations.